Preparation method of high-performance imidazolyl polyion liquid membrane
Through the preparation method of imidazolyl polyion liquid film, the problems of low ion conductivity, poor alkali resistance and low mechanical properties of the anion exchange film are solved, efficient ion transport and chemical stability are achieved, and the service life of the film is extended.
Patent Information
- Application Number
- CN202510535550.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-27
- Publication Date
- 2025-08-01
AI Technical Summary
The existing anion exchange membranes have problems such as low ion conductivity, poor alkali resistance and low mechanical properties during the electrolytic hydrogen production process, which affects their chemical stability and service life.
The preparation method of imidazolyl polyion liquid film is adopted to design the polymer structure to improve ion transport capability and mechanical properties through the hydrothermal reaction and solvent system of specific compounds, including the use of raw materials such as 2-phenylbenzimidazole, 4,4-difluorodiphenylsulfone, etc., to carry out hydrothermal reaction, solvent stirring and ion exchange treatment to form a high-performance imidazolyl polyion liquid film.
It improves the ion exchange capacity and mechanical properties, enhances the tensile strength and elongation of break of the film, reduces the swelling ratio, improves the chemical stability and ionic conductivity, and extends the service life of the film.
Smart Images

Figure FT_1 
Figure FT_2 
Figure FT_3
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of ion membrane preparation, and more specifically relates to a method for preparing a high-performance imidazole-based polyionic liquid membrane. Background Art
[0002] As an emerging clean energy source, hydrogen is considered one of the world's most promising energy sources due to its environmental friendliness, safety, and diverse application scenarios. Currently, hydrogen energy is widely used in industries such as industry, transportation, electricity, and construction, becoming a new pillar of the global energy transition. Unlike gray hydrogen produced from fossil fuels and blue hydrogen produced from natural gas, hydrogen produced by water electrolysis is called green hydrogen. It produces almost no carbon emissions and is also known as "zero-carbon hydrogen," making it the most environmentally friendly option. As awareness and actions to reduce carbon emissions and protect the ecological environment continue to grow, hydrogen produced by water electrolysis is considered the most promising energy source.
[0003] The room temperature water electrolysis hydrogen production technology mainly includes alkaline water electrolysis hydrogen production (AWE), proton exchange membrane water electrolysis hydrogen production (PEMWE) and anion exchange membrane water electrolysis hydrogen production (AEMWE). AWE uses a high concentration of alkaline solution as the electrolyte, which is easy to cause corrosion to the equipment. In addition, the electrolysis and the diaphragm are far apart, which increases the volume of the electrolyzer. The cathode / anode catalysts of the PEMWE electrolyzer mainly rely on platinum group precious metal materials with scarce reserves and high prices, and the proton exchange membrane mainly relies on fluorocarbon membranes, which increases its use cost and limits the large-scale application of PEMWE technology to a certain extent. AEMWE combines the advantages of AWE's low cost and PEMWE's high efficiency and convenience. The hydroxide ions (OH - ) replaces the hydrogen ion (H + Anion exchange membranes operating in alkaline environments require a lower redox potential and exhibit higher kinetics. This allows the use of non-platinum group metals, such as nickel and cobalt, as electrodes, achieving excellent hydrogen evolution performance. This avoids the use of platinum group precious metal electrode catalysts, significantly reducing production costs. Furthermore, the use of pure water or low-concentration alkaline solutions as electrolytes reduces the corrosive effects of strong alkaline solutions on equipment. AEMWE's cost-effectiveness, mild operating conditions, environmental friendliness, and strong adaptability have made it the most promising green hydrogen production method and are gaining market favor.
[0004] However, AEMWE is still in its early stages of development and faces many problems that need to be solved, such as chemical stability and mechanical stability. Since the operating humidity of AEMWE is close to 100% and the temperature is greater than 80°C, the anion exchange membrane easily absorbs water, resulting in a high swelling ratio, which leads to low chemical stability and a service life far lower than that of the proton exchange membrane. In addition, OH -The conductivity is also relatively low, resulting in the ionic conductivity of the anion exchange membrane being lower than that of the proton exchange membrane, which limits the ion transport efficiency and directly affects the commercial application of the anion exchange membrane. To solve these problems, it is necessary to further improve the performance of the membrane material, increase the membrane life and electrolysis efficiency, and further technological maturity and cost optimization are required. Therefore, it is particularly urgent to develop anion exchange membranes with low cost, stable chemical properties and stable mechanical properties. Summary of the Invention
[0005] The technical problem to be solved by the present invention is to overcome the defects and deficiencies in the prior art and provide a preparation method of a high-performance imidazole-based polyionic liquid membrane. This preparation method designs and optimizes the structure of the ion membrane through the structure of the imidazole-based polyionic liquid, effectively solving the problems of low ionic conductivity, poor alkali resistance and low mechanical properties. The polyionic liquid membrane prepared by this method has more ion sites, which is beneficial to ion transport and increases the ion exchange capacity. Moreover, this molecular structure has a relatively large molecular weight, enhancing the tensile strength and elongation at break, and greatly improving its chemical stability and mechanical property stability. The high-performance imidazole-based polyionic liquid membrane of the present invention has good application prospects in hydrogen production by electrolyzing water and water treatment.
[0006] The object of the present invention is to provide a preparation method of a high-performance imidazole-based polyionic liquid membrane.
[0007] The above object of the present invention is achieved by the following technical solutions: A preparation method of a high-performance imidazole-based polyionic liquid membrane, comprising the following steps: (1) Mix 2-phenylbenzimidazole or 2,4,5-triphenylimidazole, 4,4'-difluorodiphenyl sulfone, 1,4-dibromobenzene, 4,4'-dibromobiphenyl or 4,4'-dibromotriphenylbenzene and N-methylpyrrolidone evenly, then add them into a hydrothermal reaction kettle for reaction. After the reaction, wash the product with deionized water and dry it in a vacuum drying oven to obtain Product 1; (2) In a three-necked flask filled with inert gas, using dichloromethane as a solvent, add Product 1, biphenyl or p-terphenyl and N-methyl-4-piperidone, stir, slowly add an organic strong acid, and carry out a reaction. The color gradually changes from pink to purple. Pour the product into excessive methanol, and a solid precipitates to obtain Product 2; (3) Add Product 2 to an alkaline solution to remove the residual acid in the product, stir at room temperature, wash and then dry in a vacuum drying oven to obtain Product 3; (4) Dissolve Product 3 in N,N-dimethylformamide, add methyl iodide and potassium carbonate, carry out a stirring reaction, pour the product into excessive ethyl acetate, and a white solid precipitates. Wash it with deionized water and dry it in a vacuum to obtain Product 4; (5) Dissolve the product four in dimethyl sulfoxide, take the supernatant and coat it on a dry and clean glass plate, and then dry it; put the obtained polyionic liquid membrane into an alkaline solution for ion exchange to obtain a high-performance imidazolium-based polyionic liquid membrane.
[0008] Further, in step (1), the molar ratio of 2-phenylbenzimidazole or 2,4,5-triphenylimidazole to 4,4-difluorodiphenyl sulfone, 1,4-dibromobenzene, 4,4-dibromobiphenyl or 4,4-dibromotriphenyl is 2-8:2-10; the reaction conditions are that the reaction temperature is 50-300 °C and the reaction time is 3-20 hours; the drying is carried out at 50~80 °C for 10-25 h.
[0009] Further, in step (2), the molar ratio of the product one, biphenyl or p-terphenyl to N-methyl-4-piperidone is 1-7:3-12:2-15; the inert atmosphere is a nitrogen atmosphere or an argon atmosphere; the reaction temperature is -10-20 °C and the reaction time is 2-12 h.
[0010] Further, in step (2), the stirring speed is 100-800 r·min -1 ; The organic strong acid is any one or more of trichloroacetic acid, trifluoroacetic acid and trifluoromethanesulfonic acid, and is added dropwise at a rate of 0.01-10 mL·min -1 .
[0011] Further, in step (3), the alkaline solution is one of potassium carbonate solution, sodium carbonate solution, sodium bicarbonate solution, potassium bicarbonate solution, and the concentration of the solution is 0.01-15 mol·L -1 .
[0012] Further, in step (3), wash with deionized water until the pH is 6.5-7.5.
[0013] Further, in step (3), the stirring time is 5-24 h, and the drying is carried out at 50-80 °C for 10-30 h.
[0014] Further, in step (4), the product three is dissolved in N,N-dimethylformamide, the solution concentration is 0.05-10%, and the reaction is carried out in the dark; the stirring reaction is carried out at 30-50 °C for 10-40 h, and the stirring speed is 100-800r·min -1 ; The vacuum drying is carried out at 50-80 °C for 10-30 h.
[0015] Further, in step (5), the product four and dimethyl sulfoxide are made into a solution with a concentration of 0.01-15 %.
[0016] Further, in step (5), the prepared anion exchange membrane is subjected to ion exchange in 0.01 - 5 M NaOH or KOH for 5 - 72 h.
[0017] A high-performance imidazolium-based polyionic liquid membrane prepared by the preparation method of a high-performance imidazolium-based polyionic liquid membrane described above, and is used for hydrogen production by electrolyzing water.
[0018] The present invention has the following beneficial effects: (1) The polyionic liquid membrane prepared by the present invention has excellent mechanical properties. The molecular structure of the present invention has a relatively high molecular weight, and the high-molecular-weight structure can enhance the mechanical properties of the membrane and improve the tensile property of the membrane. The membrane after OH - exchange reaches a tensile strength of 60 MPa. The membrane designed by the present invention has excellent flexibility. After the polyionic liquid membrane is repeatedly folded several times, no cracks or breakage occur, and the membrane can still return to its original state. Therefore, the polyionic liquid membrane of the present invention greatly improves its tensile strength and elongation at break through the entangled polymer structure.
[0019] (2) The polyionic liquid membrane prepared by the present invention has good ionic conductivity. The membrane structure of the present invention is a polymer with multiple ionic sites, which improves the ability of ion transport. Therefore, the membrane prepared by the present invention has excellent ion exchange capacity, improves the ion conduction efficiency, and thus has a relatively high ionic conductivity.
[0020] (3) The polyionic liquid membrane prepared by the present invention has a relatively low swelling ratio. A relatively high swelling ratio results in poor alkali resistance of the membrane, affects the service life of the membrane, and increases the production cost. The membrane of the present invention avoids the problem of poor alkali resistance caused by a high swelling ratio. In 1 M KOH, the ionic conductivity hardly decreases after 1500 h. Description of the Drawings
[0021] Figure 1-12 is the composition structure of the high-performance imidazolium-based polyionic liquid membrane provided by the present invention; Figure 13 is the ionic conductivity of the high-performance polybenzimidazole-based anion exchange membrane provided by the present invention; Figure 14 is the mechanical property of the high-performance polybenzimidazole-based anion exchange membrane provided by the present invention; Figure 15 is the swelling ratio of the high-performance polybenzimidazole-based anion exchange membrane provided by the present invention; Figure 16 is the thermogravimetric diagram of the high-performance polybenzimidazole-based anion exchange membrane provided by the present invention. Detailed Embodiments
[0022] The present invention will be further described below in conjunction with specific embodiments, but the embodiments do not impose any form of limitation on the present invention. Unless otherwise specified, the reagents, methods, and equipment used in the present invention are conventional reagents, methods, and equipment in the technical field.
[0023] When an equivalent, concentration, or other value or parameter is expressed as a range, a preferred range, or a range defined by a series of upper preferred values and lower preferred values, it should be understood that all ranges formed by any pairing of any range upper limit or preferred value and any range lower limit or preferred value are specifically disclosed, regardless of whether the range is separately disclosed. For example, when the range "1 to 5" is disclosed, the described range should be interpreted to include ranges "1 to 4", "1 to 3", "1 to 2", "1 to 2 and 4 to 5", "1 to 3 and 5", etc. When a numerical range is described herein, unless otherwise stated, the range is intended to include its end values and all integers and fractions within the range.
[0024] The indefinite articles "a" and "an" before the elements or components of the present invention do not limit the quantity requirements (i.e., the number of occurrences) of the elements or components. Therefore, "a" or "an" should be interpreted to include one or at least one, and the singular form of the element or component also includes the plural form, unless the quantity clearly refers only to the singular form.
[0025] In addition, the descriptions of the terms "one embodiment", "some embodiments", "examples", etc. in the present invention mean that the specific features, structures, materials, or characteristics described in connection with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic descriptions of the above terms are not necessarily directed to the same embodiment or example. Moreover, the technical features involved in various embodiments of the present invention can be combined with each other as long as they do not conflict with each other.
[0026] Unless otherwise specified, the reagents and materials used in the following examples are all commercially available.
[0027] Example 1 (1) After uniformly mixing 1.48 g (5 mmol) of 2,4,5-triphenylimidazole, 1.87 g (8 mmol) of 1,4-dibromobenzene, and 30 mL of N-methylpyrrolidone, the mixture was added to a reaction kettle. At 100 °C, the reaction was carried out for 6 h. After the reaction, the product was washed 5 times with deionized water and dried at 80 °C in a vacuum drying oven for 24 h to obtain product A2B1.
[0028] (2) In a three-necked flask filled with a nitrogen atmosphere, 20 ml of dichloromethane, 0.924 g (2 mmol) of A2B1, 0.57 g (5 mmol) of N-methyl-4-piperidone, and 0.31 g (2 mmol) of biphenyl were uniformly mixed and reacted for 1.5 h, and then at 1 mL·min-1 20 mL of trifluoromethanesulfonic acid was added dropwise at a certain speed, and the solution was stirred with a mechanical stirrer at 0 °C. After reacting for 4 h, the solution gradually changed from pink to a purple viscous substance. The product was poured into excess methanol to obtain a white precipitate.
[0029] (3) The white precipitate obtained in step (2) was added to a 0.1 M potassium carbonate solution, stirred at room temperature for 10 h, washed 5 times with deionized water, and then dried in a vacuum drying oven at 80 °C for 12 h to obtain product A2B1C1.
[0030] (4) After mixing 1 g of product A2B1C1 evenly with 10 mL of N,N-dimethylformamide, 0.1 g of potassium carbonate and 0.3 mL of methyl iodide were added. After reacting in the dark for 12 h, it was poured into ethyl acetate, and a white solid precipitated. After washing 3 times with deionized water, it was then dried in a vacuum drying oven at 80 °C for 24 h to obtain product A2B1C1-I.
[0031] (5) Product A2B1C1-I was dissolved in dimethyl sulfoxide to prepare a 0.5% solution, then coated on a clean glass plate, heated at 120 °C for 12 h to obtain a film. The film was placed in 0.5 M NaOH for ion exchange for 12 h to obtain the polyionic liquid membrane A2B1C1-OH.
[0032] The anion exchange membrane prepared in Example 1 was used, and all electrochemical measurements were carried out on a Shanghai Chenhua CHI 760E electrochemical workstation. The ionic conductivity test was measured using a Chenhua ionic conductivity test fixture. Under four electrodes, the open circuit voltage was used as the test voltage for impedance, and the impedance test was carried out at different temperatures. The ionic conductivity test formula is: . Where L is the distance between the working electrode and the counter electrode, R is the measured impedance, and A is the cross-sectional area of the membrane. The mechanical properties of the anion exchange membrane were tested on a thin film tensile machine. The thin film was cut into a dumbbell shape, and the test speed was 2 mm·min -1 . The swelling ratio and water absorption rate test of the anion exchange membrane was to place the anion exchange membrane in pure water at different temperatures. After 24 h, the water on the surface of the membrane was wiped off, and their length (L wet ) and weight (W wet ) were quickly recorded. Subsequently, the anion exchange membrane was dried at 80 °C for 24 h, and the length (L dry ) and weight (W dry ) were recorded. The water absorption rate calculation formula is: , and the swelling ratio calculation formula is: .
[0033] Figure 13Ionic conductivity graph of the imidazole-based polyionic liquid membrane prepared in Example 1. As the temperature increases, the ionic conductivity gradually increases. When the temperature is 30 °C, the ionic conductivity is greater than 100 mS·cm -1 , and when the temperature rises to 80 °C, the ionic conductivity is higher than 200 mS·cm -1 . The increase in temperature greatly promotes the transport of OH - ions, thereby increasing the ion exchange capacity and effectively improving the ionic conductivity. Compared with other anion exchange membranes, the anion exchange membrane of the present invention has an absolute advantage in ionic conductivity value.
[0034] Figure 14 Mechanical property graph of the imidazole-based polyionic liquid membrane prepared in Example 1 for water electrolysis. At a tensile speed of 2 mm·min -1 , the tensile strength of the anion exchange membrane after OH - exchange was measured to be 63.56 MPa, and the elongation at break was 66.92%. It is much higher than the mechanical property tests of other anion exchange membranes. It shows that the anion exchange membrane prepared by the present invention has excellent mechanical property stability.
[0035] Figure 15 Swelling ratio graph of the imidazole-based polyionic liquid membrane prepared in Example 1. As the temperature increases, the swelling ratio of the polyionic liquid membrane gradually increases, and the increase is relatively small. This is mainly related to the branched chains of the polymer structure, and the branched structure limits the swelling of the anion exchange membrane in the present invention. The relatively low swelling ratio of the anion exchange membrane is beneficial to improving the chemical stability of the membrane and increasing the service life of the anion exchange membrane.
[0036] Such as Figure 16 Thermogravimetric graph of the imidazole-based polyionic liquid membrane prepared in Example 1. At a rate of 10 °C·min -1 , the test was carried out between 0 °C and 800 °C. Before 300 °C, the polyionic liquid membrane decreased by about 10%, including a small amount of loss due to trace moisture. When heated to 800 °C, the mass loss of the polyionic liquid membrane of the present invention was about 50%. The mass loss between 300 - 400 °C was caused by the degradation of cationic groups and side chains. The mass loss between 500 - 650 °C was caused by the degradation of the polymer main chain.
[0037] Example 2 (1) After mixing 0.97 g (5 mmol) of 2-phenylbenzimidazole, 2.50 g (8 mmol) of 4,4'-dibromobiphenyl and 30 mL of N-methylpyrrolidone evenly, add them to a reaction kettle. React at 100 °C for 6 h. After the reaction, wash the product 5 times with deionized water and dry it in a vacuum drying oven at 80 °C for 24 h to obtain product A1B2.
[0038] (2) In a three-necked flask filled with a nitrogen atmosphere, 20 ml of dichloromethane, 0.924 g (2 mmol) of product A1B2, 0.57 g (5 mmol) of N-methyl-4-piperidone, and 0.31 g (2 mmol) of biphenyl were uniformly mixed and reacted for 1.5 h, and then 20 mL of trifluoromethanesulfonic acid was added dropwise at a rate of 1 mL·min -1 and the solution was stirred with a mechanical stirrer at 0 °C. After reacting for 4 h, the solution gradually changed from pink to a purple viscous substance. The product was poured into excess methanol to obtain a white precipitate.
[0039] (3) The white precipitate in step (2) was added to 0.1 M potassium carbonate solution and stirred at room temperature for 10 h. After washing 5 times with deionized water, it was dried in a vacuum drying oven at 80 °C for 12 h to obtain product A1B2C1.
[0040] (4) After uniformly mixing 1 g of product A1B2C1 with 10 mL of N,N-dimethylformamide, 0.1 g of potassium carbonate and 0.3 mL of iodomethane were added. After reacting in the dark for 12 h, it was poured into ethyl acetate, and a white solid precipitated. After washing 3 times with deionized water, it was dried in a vacuum drying oven at 80 °C for 24 h to obtain product A1B2C1-I.
[0041] (5) Product A1B2C1-I was dissolved in dimethyl sulfoxide to form a 0.5% solution, then coated on a clean glass plate and heated at 120 °C for 12 h to obtain a film. The film was placed in 0.5 M NaOH for ion exchange for 12 h to obtain polyionic liquid membrane A1B2C1-OH. The tensile strength of the polyionic liquid membrane A1B2C1-OH was measured to be 62.84 MPa, and the elongation at break was 67.13%.
[0042] Example 3 (1) 1.48 g (5 mmol) of 2,4,5-triphenylimidazole, 2.50 g (8 mmol) of 4,4-dibromobiphenyl, and 30 mL of N-methylpyrrolidone were uniformly mixed and then added to a reaction kettle. The reaction was carried out at 100 °C for 6 h. After the reaction, the product was washed 5 times with deionized water and dried in a vacuum drying oven at 80 °C for 24 h to obtain product A2B2.
[0043] (2) In a three-necked flask filled with a nitrogen atmosphere, 20 mL of dichloromethane, 1.08 g (2 mmol) of A2B2, 0.57 g (5 mmol) of N-methyl-4-piperidone, and 1.38 g (8 mmol) of p-terphenyl were uniformly mixed and reacted for 1.5 h, and then at a rate of 1 mL·min -120 mL of trifluoromethanesulfonic acid was added dropwise at a rate of, and the solution was stirred with a mechanical stirrer at 0 °C. After reacting for 4 h, the solution gradually changed from pink to a purple viscous substance. The product was poured into an excess of methanol to obtain a white precipitate.
[0044] (3)The white precipitate obtained in step (2) was added to a 0.1 M potassium carbonate solution and stirred at room temperature for 10 h. After washing 5 times with deionized water, it was dried in a vacuum drying oven at 80 °C for 12 h to obtain the product A2B2C2.
[0045] (4)After mixing 1 g of the product A2B2C2 evenly with 10 mL of N,N-dimethylformamide, 0.1 g of potassium carbonate and 0.3 mL of iodomethane were added. After reacting in the dark for 12 h, it was poured into ethyl acetate, and a white solid precipitated out. After washing 3 times with deionized water, it was dried in a vacuum drying oven at 80 °C for 24 h to obtain the product A2B2C2-I.
[0046] (5)The product A2B2C2-I was dissolved in dimethyl sulfoxide to form a 0.5% solution, and then coated on a clean glass plate. After heating at 120 °C for 12 h, a film was obtained. The film was put into 0.5 M NaOH for ion exchange for 12 h to obtain the polyionic liquid membrane A2B2C2-OH. The tensile strength of the polyionic liquid membrane A2B2C2-OH was measured to be 63.33 MPa, and the elongation at break was 67.06%.
[0047] Example 4 (1)1.48 g (5 mmol) of 2,4,5-triphenylimidazole, 3.09 g (8 mmol) of 4,4'-dibromotriphenyl and 30 mL of N-methylpyrrolidone were mixed evenly and then added to a reaction kettle. The reaction was carried out at 100 °C for 6 h. After the reaction, the product was washed 5 times with deionized water and dried in a vacuum drying oven at 80 °C for 24 h to obtain the product A2B3.
[0048] (2)In a three-necked flask filled with a nitrogen atmosphere, 20 mL of dichloromethane, 1.23 g (2 mmol) of A2B3, 0.57 g (5 mmol) of N-methyl-4-piperidone and 0.31 g (2 mmol) of biphenyl were evenly mixed and reacted for 1.5 h, and then added dropwise at a rate of 1 mL·min -1 20 mL of trifluoromethanesulfonic acid was added dropwise at a rate of, and the solution was stirred with a mechanical stirrer at 0 °C. After reacting for 4 h, the solution gradually changed from pink to a purple viscous substance. The product was poured into an excess of methanol to obtain a white precipitate.
[0049] (3) Add the white precipitate obtained in step (2) to a 0.1 M potassium carbonate solution and stir for 10 h at room temperature. After washing 5 times with deionized water, dry in a vacuum drying oven at 80 °C for 12 h to obtain product A2B3C1.
[0050] (4) Mix 1 g of product A2B3C1 evenly with 10 mL of N,N-dimethylformamide, then add 0.1 g of potassium carbonate and 0.3 mL of methyl iodide. After reacting for 12 h in the dark, pour it into ethyl acetate. White solid precipitates out. After washing 3 times with deionized water, dry in a vacuum drying oven at 80 °C for 24 h to obtain product A2B3C1-I.
[0051] (5) Dissolve product A2B3C1-I in dimethyl sulfoxide to prepare a 0.5% solution, then coat it on a clean glass plate. After heating at 120 °C for 12 h, the film obtained is immersed in 0.5 M NaOH for ion exchange for 12 h to obtain polyionic liquid membrane A2B3C1-OH. The tensile strength of polyionic liquid membrane A2B3C1-OH is measured to be 64.15 MPa, and the elongation at break is 66.45%.
[0052] Example 5 (1) Mix 1.48 g (5 mmol) of 2,4,5-triphenylimidazole, 2.03 g (8 mmol) of 4,4'-difluorodiphenyl sulfone and 30 mL of N-methylpyrrolidone evenly, then add them to a reaction kettle and react at 100 °C for 6 h. After the reaction, wash the product 5 times with deionized water and dry in a vacuum drying oven at 80 °C for 24 h to obtain product A2B4.
[0053] (2) In a three-necked flask filled with a nitrogen atmosphere, mix 20 mL of dichloromethane, 1.20 g (2 mmol) of A2B4, 0.57 g (5 mmol) of N-methyl-4-piperidone and 0.31 g (2 mmol) of biphenyl evenly and react for 1.5 h. Then, add 20 mL of trifluoromethanesulfonic acid dropwise at a rate of 1 mL·min -1 and stir the solution with a mechanical stirrer at 0 °C. After reacting for 4 h, the solution gradually changes from pink to purple viscous substance. Pour the product into excessive methanol to obtain a white precipitate.
[0054] (3) Add the white precipitate obtained in step (2) to a 0.1 M potassium carbonate solution and stir for 10 h at room temperature. After washing 5 times with deionized water, dry in a vacuum drying oven at 80 °C for 12 h to obtain product A2B4C1.
[0055] (4) After mixing 1 g of product A2B4C1 evenly with 10 mL of N,N-dimethylformamide, 0.1 g of potassium carbonate and 0.3 mL of methyl iodide were added. After reacting for 12 h in the dark, it was poured into ethyl acetate, and white solid precipitated out. After washing 3 times with deionized water, it was dried in a vacuum drying oven at 80 °C for 24 h to obtain product A2B4C1-I.
[0056] (5) Product A2B4C1-I was dissolved in dimethyl sulfoxide to form a 0.5% solution, then coated on a clean glass plate and heated at 120 °C for 12 h to obtain a film. The film was put into 0.5 M NaOH for ion exchange for 12 h to obtain polyionic liquid membrane A2B4C1-OH. The tensile strength of polyionic liquid membrane A2B4C1-OH was measured to be 64.31 MPa, and the elongation at break was 65.87%.
[0057] The above embodiments are preferred embodiments of the present invention, but the embodiments of the present invention are not limited to the above embodiments. Any other changes, modifications, substitutions, combinations, and simplifications made without departing from the spirit and principle of the present invention shall be equivalent replacement methods and are all included in the protection scope of the present invention.
Claims
1. A preparation method of a high-performance imidazole-based polyionic liquid membrane, characterized in that, It includes the following steps: (1) Mix 2-phenylbenzimidazole or 2,4,5-triphenylimidazole, 4,4'-difluorodiphenyl sulfone, 1,4-dibromobenzene, 4,4'-dibromobiphenyl or 4,4'-dibromotriphenyl in N-methylpyrrolidone uniformly, then add them into a hydrothermal reactor for reaction. After the reaction, wash the product with deionized water and dry it in a vacuum drying oven to obtain Product 1; (2) In a three-necked flask filled with inert gas, using dichloromethane as a solvent, add Product 1, biphenyl or p-terphenyl and N-methyl-4-piperidone, stir, slowly add an organic strong acid for reaction. The color gradually changes from pink to purple. Pour the product into excessive methanol, and a solid precipitates to obtain Product 2; (3) Add Product 2 into an alkaline solution to remove the residual acid in the product, stir at room temperature, wash and then dry in a vacuum drying oven to obtain Product 3; (4) Dissolve Product 3 in N,N-dimethylformamide, add methyl iodide and potassium carbonate, stir for reaction, pour the product into excessive ethyl acetate, a white solid precipitates, wash it with deionized water and dry it in vacuum to obtain Product 4; (5) Dissolve Product 4 in dimethyl sulfoxide, take the supernatant and coat it on a clean and dry glass plate, then dry it; put the obtained polyion liquid membrane into an alkaline solution for ion exchange to obtain a high-performance imidazolium-based polyion liquid membrane.
2. The preparation method according to claim 1, wherein In step (1), the molar ratio of 2-phenylbenzimidazole or 2,4,5-triphenylimidazole to 4,4'-difluorodiphenyl sulfone, 1,4-dibromobenzene, 4,4'-dibromobiphenyl or 4,4'-dibromotriphenyl is 2-8:2-10; the reaction conditions are that the reaction temperature is 50-300 °C and the reaction time is 3-20 hours; the drying is carried out at 50-80 °C for 10-25 h.
3. The preparation method according to claim 1, wherein, In step (2), the molar ratio of Product 1, biphenyl or p-terphenyl to N-methyl-4-piperidone is 1-7:3-12:2-15; the inert atmosphere is a nitrogen atmosphere or an argon atmosphere; the reaction temperature is -10-20 °C for 2-12 h.
4. The preparation method according to claim 1, wherein In step (2), the stirring speed is 100 - 800 r·min -1 ; the organic strong acid is any one or more of trichloroacetic acid, trifluoroacetic acid, and trifluoromethanesulfonic acid, and is added dropwise at a rate of 0.01 - 10 mL·min -1 .
5. The preparation method according to claim 1, wherein In step (3), the alkaline solution is one of potassium carbonate solution, sodium carbonate solution, sodium bicarbonate solution, and potassium bicarbonate solution, and the concentration of the solution is 0.01-15 mol·L -1 .
6. The preparation method according to claim 1, characterized in that, In step (3), wash with deionized water until the pH is 6.5-7.
5.
7. The preparation method according to claim 1, characterized in that, In step (3), the stirring time is 5-24 h, and the drying is carried out at 50-80 °C for 10-30 h.
8. The preparation method according to claim 1, wherein In step (4), product III is dissolved in N,N-dimethylformamide, and the solution concentration is 0.05-10%, and the reaction is carried out in the dark; the stirring reaction is carried out at 30-50 °C for 10-40 h, and the stirring speed is 100-800 r·min -1 ; the vacuum drying is carried out at 50-80 °C for 10-30 h.
9. The preparation method according to claim 1, characterized in that, In step (5), Product 4 and dimethyl sulfoxide are made into a solution with a concentration of 0.01-15%.
10. The preparation method according to claim 1, characterized in that, In step (5), the prepared anion exchange membrane is ion-exchanged in 0.01-5 M NaOH or KOH for 5-72 h.